Perspektif Mahasiswa Baru tentang Penggunaan Sistem Pengelolaan Pembelajaran: Studi Kasus di Universitas Negeri - Aditya Permadi; Andi Kasman; Ari Ganjar Herdiansah; Sudarma Sudarma (Fakultas Seni Rupa dan Desain ITB, 2026)
This study assesses a learning management system (LMS) from the viewpoint of firstyear students, focusing on their level of acceptance toward LMS usage. Notably, 65.81% of respondents have been familiar with online learning platforms since junior high school, indicating a high degree of digital experience. During university orientation, students were introduced to the LMS through various learning activities, including campus introduction modules, online quizzes, and assignment submissions. To assess usability, data were gathered from 2,267 students who used a Likert scale to complete the System Usability Scale (SUS) questionnaire. Quantitative and descriptive analyses produced an overall SUS score of 57.57, placing the LMS within the Low Acceptance Range and corresponding to an interpretation scale of E and an “OK” adjective rating. These results suggest that, despite their digital familiarity, students found the LMS somewhat complicated and occasionally difficult to navigate. The findings highlight an urgent need for institutions to simplify learning instructions and integrate structured LMS usage guidelines into course syllabi to support students’ learning processes and reduce potential disengagement or dropout. Additionally, universities must strengthen outreach and training initiatives that enhance students’ comfort and confidence when using the LMS. LMS management in higher education essentially consists of two main aspects: ease of use and support for users, students, and faculty. This, in turn, will improve the quality of teaching and learning. Ultimately, well-managed LMS implementation will enable higher education institutions to adopt more progressive and effective hybrid learning models that align with the expectations and needs of today’s digitally oriented student generation.